Pemberdayaan KUB "Harapan Jaya" Melalui Diversifikasi Produk Olahan Kelapa Berbasis Zero Waste Concept di Desa Regei Lestari Kabupaten Kotawaringin Timur - Lili Winarti; Rokhman Permadi; Sari Hayati; Ruslan Ruslan; Ristyana Natalia (I-Com: Indonesian Community Journal, 2024)
The village of Regei Lestari, located in Teluk Sampit Subdistrict, faces significant economic and environmental challenges due to poorly managed coconut waste. This community service program aims to empower the wives of farmers, particularly members of KUB Harapan Jaya, through the implementation of the zero waste concept, transforming coconut waste into value-added products such as composters, nata de coco, and kokedama crafts. The program's implementation methods include socialization, training, and mentoring focused on enhancing management knowledge and skills as well as waste processing techniques. The results of the program show a significant increase in participants' knowledge and skills, which has the potential to improve family economic conditions and reduce negative environmental impacts. This program is essential because it not only enhances the economic welfare of the community but also promotes environmental sustainability through better waste management. In conclusion, the program successfully achieved its objectives in empowering the community and providing long-term benefits to Regei Lestari Village.